Chalconas metoxiladas bioativas : critalização, estrutura e arranjo supramolecular - Carvalho Júnior, Paulo de Sousa (2012)
The Chalcones and their derivatives are α, β unsaturated ketones. Structurally, they are open chain flavonoids containing the reactive –CO–CH=CH– fragment connecting aromatic rings. The aromatic substitution results in interesting compounds such as methoxylated chalcones that shows anti-inflammatory, anti-cancer, anti-oxidant activity. This dissertation shows the main of crystallographic elucidation concepts and objectives know the crystal structure of five methoxylated chalcones. Crystallographically, the chalcone molecule is not planar due the C-H...O supramolecular arrangement. This behavior is evidenced by the angle between the two aromatic rings. However, as methox groups are added to the molecule, different intermolecular contacts come into existence. The methoxylated chalcones (1) display similar arrangement to structural core of chalcone, both conformational and supramolecular. The dimethoxylated chalcones is more planar, the B-para- substitution contributes substantially with conformation, while the meta-orientation (compound 2a) to B ring gives C-H...O contacts along opposite directions that twist the molecular core at 10,5º. The methoxylated chalcones (E)-3-(3,5-dimethoxyphenyl)-1-(4-methoxyphenyl)prop-2-en-1-ona crystallize in the centrosymmetric space group R3 . In the crystal structure there is a disordered solvent molecule in the vacancies of lattice. The compound (3) is completely planar and express C-H...O and π-π interactions that contributes with the planar conformation. In addition, this arrangement creates a non-classical dimer. On the other hand, the ethyl substitution in the B-ring (compound 4) results in a molecule that crystallize in the P21/c space group, with the aromatic rings twisted at 15,4º as consequence of absence of relevant interactions in the B-ring.